The manifesto project - Hazelton, Rebecca, 1978-; Parker, Alan Michael, 1961- (Akron series in contemporary poetics., 2017)
The poetic manifesto has a long, rich history that hasn't been updated until now. What does a poetic manifesto look like in a time of increased pluralism, relativism, and danger? How can a manifesto open a space for new and diverse voices? Forty-five poets at different stages of their careers contribute to this new anthology, demonstrating the relevance of the declarative form at the intersection of aesthetics and politics. The contributors also have chosen their own poems to accompany their manifestos-an anthologizing act that poets are never permitted. Invaluable for writers at any stage in their careers, this anthology may be especially useful for teachers of creative writing, both undergraduate and graduate.